If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 5) = -1 Reorder the terms: -1(5 + x) = -1 (5 * -1 + x * -1) = -1 (-5 + -1x) = -1 Solving -5 + -1x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = -1 + 5 -1x = -1 + 5 Combine like terms: -1 + 5 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 | | 2(1[3u-7]1)=16 | | 2,5x-21=14 | | -4.6y=9.2 | | (8x^4-42x^2-10x)-3=0 | | 1-7(-2-8a)=-433 | | (-2)+(-3)+(-2)= | | 0,5x-3=15 | | -2x+1=-18 | | 3x-4(x-8)=34 | | (-5)+(-4)+(-2)= | | y=6x+33 | | 2x^3+9x^2+7x-24=0 | | 2(x-2)=-3x+36 | | -a-3+7=a | | -5+-4+-2= | | 2x^3+2x^2-9x-18=0 | | 170=5-3(1+7x) | | x+1-2=8 | | 7+(-25)+28= | | t=45+3.57 | | 4w-9+9=-37 | | [-15+(-8)]+6= | | x(x+10)=875 | | 3-11x=-63 | | 8500=10,093.73*r | | 6x+3=9x-5 | | 3x-12=24-9x | | 11y-12y=12 | | [-18+(-3)]+4= |